(untitled) (American Journal of Interdisciplinary Research and Development, 2024)
The concept of entrepreneurship, which is based on the concept of goal-oriented activity, includes all types of entrepreneurships, including human entrepreneurship and its own work. In this regard, business cannot be exempted from regularity. But this does not mean that human creativity is equal to other types of it, for example, the creativity of domesticated animals. They are individual and their individuality (in the work of a certain unit) is fundamentally important for characterizing human activity.